QUALITY OF INFECTIOUS DISEASE SURVEILLANCE IN PRIMARY HEALTH CARE - Predrag Duric; Svetlana Ilić (Sri Lankan Journal of Infectious Diseases, 2012)
The aim of the study was to analyse participation of primary care physicians in infectious disease surveillance and to find factors which influence the primary health physician’s participation in surveillance. Infectious disease reporting by 854 primary care physicians from 15 primary care institutions in South Bačka district, AP Vojvodina, Serbia was monitored during a 6 month period. The number and structure of infectious disease reporting through the mandatory surveillance system was compared with the number and structure of infectious diseases reported through routine statistics and the number and structure of infectious diseases reported in the whole area, including reports from secondary and tertiary health care settings and laboratories. The youngest and oldest physicians reported the lowest average number of infectious diseases. Paediatricians and dermatologists had the highest and emergency specialists, occupational medicine specialists and other consultants the lowest average number of reported infectious diseases, with the ratio between paediatricians and emergency medicine specialists being 347:1. Lowest reporting rate was observed for infections routinely diagnosed in clinics such as hepatitis, or with ethical considerations such as sexually transmitted infections. The average weekly number of reported infectious diseases was from 0.0 per emergency medicine specialists to 1.4 per paediatrician. Completeness of infectious disease surveillance in primary health care is unsatisfactory. Changing currently insufficient undergraduate and postgraduate training in surveillance might be an important tool for establishing a more effective and sensitive surveillance system. Guidelines for laboratory confirmation and reporting could also increase quality of surveillance. DOI: http://dx.doi.org/10.4038/sljid.v2i2.4325 Sri Lankan Journal of Infectious Diseases Vol.2(2) 2012: 37-46